Changes in the Liver’s Detoxification Function under Experimental Immunosuppression and its Significance in Drug Metabolism - Jurayeva Barno G’ulom qizi; Fozilova Ruxshona; Aminjonova Munisa (American Journal of Biomedicine and Pharmacy, 2025)
The liver plays a central role in detoxification and drug metabolism, maintaining systemic homeostasis by biotransforming endogenous and exogenous compounds. Experimental immunosuppression alters hepatic function, influencing enzymatic activity, metabolic clearance, and susceptibility to xenobiotic toxicity. This study evaluates changes in hepatic detoxification pathways under pharmacologically induced immunosuppression, examining cytochrome P450 activity, phase II conjugation reactions, and antioxidant defense mechanisms. Findings demonstrate that immunosuppressed conditions reduce metabolic efficiency, alter drug clearance rates, and increase oxidative stress, underscoring the importance of monitoring hepatic function in immunocompromised subjects. Understanding these changes is essential for optimizing therapeutic regimens, adjusting dosages, and preventing drug-related complications in clinical and experimental settings. The hepatic detoxification system represents a critical defense mechanism responsible for metabolizing endogenous compounds, xenobiotics, and pharmacological agents, thereby preserving systemic homeostasis. Experimental induction of immunosuppression substantially modifies these processes, affecting enzymatic activity, metabolic efficiency, and oxidative balance. This study evaluates alterations in phase I and phase II detoxification pathways, cytochrome P450-mediated oxidation, conjugation reactions, and antioxidant defense under controlled immunosuppressive conditions. Results indicate significant reduction in substrate metabolism, impaired clearance of xenobiotics, and elevated oxidative stress, demonstrating compromised hepatic resilience. Understanding these modifications is essential for optimizing pharmacotherapy, preventing accumulation of toxic intermediates, and ensuring organ protection in immunocompromised states.